2019
DOI: 10.1111/ijfs.14131
|View full text |Cite
|
Sign up to set email alerts
|

In vitro potential of flavonoids from tartary buckwheat on antioxidants activity and starch digestibility

Abstract: Summary The effects of various flavonoids of Tartary buckwheat (rutin‐enhanced flavonoid extract [REFE and quercetin‐enhanced flavonoid extract [QEFE]) and individual flavonoids (rutin, quercetin and kaempferol) on the antioxidant activity, inhibition of α‐glucosidases and α‐amylase and starch digestibility were evaluated. Quercetin possessed the highest antioxidant activity and inhibition of α‐glucosidases and α‐amylase activity followed by kaempferol and rutin. REFE and QEFE have similar antioxidant and inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Peng et al. (2019) prepared extracts enriched with rutin and quercetin from tartary buckwheat flour, of which the radical scavenging ability was evidently lower than the highest values at present work. The most likely cause for the discrepancy should be the varying extracting concentration of phenolics.…”
Section: Resultsmentioning
confidence: 46%
“…Peng et al. (2019) prepared extracts enriched with rutin and quercetin from tartary buckwheat flour, of which the radical scavenging ability was evidently lower than the highest values at present work. The most likely cause for the discrepancy should be the varying extracting concentration of phenolics.…”
Section: Resultsmentioning
confidence: 46%
“…The taste and digestibility of buckwheat could be improved because of the increase of reducing sugar. In our study, the trend in carbohydrate content was gradually decreasing, while some studies have shown that the flavonoids in buckwheat (rutin, quercetin, and kaempferol) inhibit the activity of α-amylase, which leads to a slower rate of starch breakdown (5). Therefore, whether the increase in flavonoid content of buckwheat sprouts obtained by the PAW treatment decreases the rate of carbohydrate decomposition remains to be studied subsequently.…”
Section: Discussionmentioning
confidence: 62%
“…( 3 , 4 ). It is rich in flavonoids ( 5 ), phenols ( 6 ), proteins and peptides ( 7 ), sugar alcohols, D-Chiral inositol ( 8 ), polysaccharides ( 9 ), steroids, and other bioactive substances, which has a high antioxidant effect by inhibiting the oxidative stress, beneficial to the prevention and treatment of cardiovascular disease, and reduce triglycerides ( 10 ), total cholesterol, so it has a very good healthcare, medicinal value ( 11 ). However, there is fagopyrin substance in buckwheat, which is a phototoxic naftodianthrone related to hypericin ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…DPPH, ABTS radical scavenging activities, as well as FRAP methods were used to evaluate the antioxidant activities of extracts. Tartary buckwheat has strong DPPH and ABTS radical scavenging activities (Peng et al., 2019). DPPH values were shown in Table 3, DPPH values of 80% acetone, ethyl acetate, and 70% ethanol extracts ranged from 1,996.8 ± 46.3 to 2,772.8 ± 168.3 mg TE/100 g DW, 63.414 ± 1.706 to 112.39 ± 2.95 mg TE/100 g DW, and 2,683.3 ± 79.9 to 3,091.7 ± 19.6 mg TE/100 g DW, respectively.…”
Section: Resultsmentioning
confidence: 99%